Effects of Education and Health and Unemployment against Poverty in Bangka Belitung Islands - Chammearc, Hasdiar B.; Ratnasih, Cicih (Jurnal Indonesia Sosial Sains, 2023)
One of the main indicators of successful development is the decline in the number of poor people. This study aims to analyze the effect of education, health and unemployment on poverty rates in the Bangka Belitung Islands province in 2010-2021. This research is quantitative. The data used in this study are secondary data obtained from the Central Statistics Agency with cross section 7 districts / cities in Bangka Belitung Islands and time series for 12 (twelve) years. Analysis of the data used is panel data analysis with a random effect model. Data is processed by using Eviews 12. The results showed that: (1) Education had a significant negative effect on the poverty rate in Bangka Belitung Islands Province; (2) Health and positive influence are not significant on poverty rates in Bangka Belitung Islands Province; (3) Unemployment does not have a significant effect on the poverty rate in Bangka Belitung Islands Province.